(untitled) (ASEAN Engineering Journal, 2021)
This paper proposes a fuzzy logic algorithm that evaluates the indoor environmental conditions on an urban bus specifically in Metro Manila. This algorithm identifies the value of three indexes: IAQI, TCI, and CO2. The Indoor Air Quality Index (IAQI) quantifies the level of indoor air quality of the bus. CO2, CO, NO2, O3, TVOC, and PM10 are the input parameters for the fuzzy logic system that will determine IAQI. Thermal Comfort Index (TCI) quantifies the indoor thermal condition in four levels. The indoor temperature and humidity are the input parameters for the fuzzy logic system that will determine TCI. The fuzzy logic program in this study is designed mainly for the bus ventilation control system. The created FLS program was able to give good results. The observations from the program were the following: as the indoor air pollutants increased, the IAQI decreased; as the level of thermal parameters increased, the TCI decreased; and as the CO2 level and temperature increased, the number of passengers also increased.